2010
DOI: 10.1161/hypertensionaha.109.145391
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Sensitizes Rats to Angiotensin II–Induced Hypertension and Vascular Inflammation in Adult Life

Abstract: Abstract-Maternal separation during early life is an established chronic behavioral model of early life stress in rats. It is known that perinatal adverse environments increase activity of the renin-angiotensin (Ang) system, specifically Ang II, in adulthood. The aim of this study was to investigate whether the effects of early life stress augment the sensitivity of the Ang II pathway. Using Wistar Kyoto rats, the maternal separation (MS) protocol was performed by separating approximately half of the male pups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 43 publications
4
82
0
1
Order By: Relevance
“…In rodents, maternal separation has been used to study the influence of chronic behavioral stress, and we reasoned that this model resembles, in part, an adverse environment during early life that may increase susceptibility to cardiovascular disease. Interestingly, the MS model does not appear to induce significant baseline differences in the cardiovascular phenotype in rats (33,47). Consistent with our report, several studies in rodents demonstrate that MS does not affect locomotor activity (4,19,27,45).…”
Section: Discussionsupporting
confidence: 91%
“…In rodents, maternal separation has been used to study the influence of chronic behavioral stress, and we reasoned that this model resembles, in part, an adverse environment during early life that may increase susceptibility to cardiovascular disease. Interestingly, the MS model does not appear to induce significant baseline differences in the cardiovascular phenotype in rats (33,47). Consistent with our report, several studies in rodents demonstrate that MS does not affect locomotor activity (4,19,27,45).…”
Section: Discussionsupporting
confidence: 91%
“…Our study reports associations between early adversity and DNAm in adulthood in a non-Western, lower income setting. Furthermore, our findings are consistent with experimental animal models documenting durable effects of maternal separation on the regulation of inflammation (50)(51)(52).…”
Section: Discussionsupporting
confidence: 89%
“…Neonatal rats were subject to the MS stress protocol, as previously described (35,40), with litter sizes culled to 10 pups/litter. Neonates were separated from their mothers and placed in a heated cage (30°C) for 3 h/day from PND2-14.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies by Pollock and coworkers showed that rats exposed to this ELS had normal resting BP as adults, but exaggerated acute pressor responses to norepinephrine (37) and hypertensive responses to chronic angiotensin II infusion (39,40). Their studies implicated changes in arterial and kidney function in the relationship between ELS and adult hypertension (38).…”
Section: There Is Increasing Interest In Developmental Programming Ofmentioning
confidence: 99%